Nitric oxide is an obligate bacterial nitrification intermediate produced by hydroxylamine oxidoreductase - Caranto, Jonathan D; Lancaster, Kyle M (Proceedings of the National Academy of Sciences - PNAS, 2017)
Ammonia (NH )-oxidizing bacteria (AOB) emit substantial amounts of nitric oxide (NO) and nitrous oxide (N O), both of which contribute to the harmful environmental side effects of large-scale agriculture. The currently accepted model for AOB metabolism involves NH oxidation to nitrite (NO ) via a single obligate intermediate, hydroxylamine (NH OH). Within this model, the multiheme enzyme hydroxylamine oxidoreductase (HAO) catalyzes the four-electron oxidation of NH OH to NO We provide evidence that HAO oxidizes NH OH by only three electrons to NO under both anaerobic and aerobic conditions. NO observed in HAO activity assays is a nonenzymatic product resulting from the oxidation of NO by O under aerobic conditions. Our present study implies that aerobic NH oxidation by AOB occurs via two obligate intermediates, NH OH and NO, necessitating a mediator of the third enzymatic step.